Regulatory role of circular RNAs in oral squamous cell carcinoma: Role of circular RNAs in the progression of OSCC - Attar, Rukset; Noel, Khalida; Romero, Mirna Azalea; Sabitaliyevich, Uteuliyev Yerzhan; Yulaevna, Ishmuratova Margarita; Qureshi, Muhammad Zahid (Cellular and Molecular Biology, 2023)
OSCC is a genomically complicated disease and advancements in the modern era of molecular oncology have enabled researchers to portray near-to-complete resolution of signaling landscape. Over the last two decades, overwhelming proof-of-concept has established mechanistic regulatory role of non-coding RNAs in carcinogenesis, including OSCC. Circular RNAs demonstrate a burgeoning facet of oncology research and molecular biologists are only beginning to appreciate and recognize the significance of circRNAs in the pathogenesis of OSCC. Regulatory roles of non-coding RNAs in the re-shaping of signaling pathways offer plausible strategies for prevention/inhibition of OSCC. Circular RNAs have mechanistic roles in OSCC and "sponge effects" mediated by a wider variety of circRNAs need to be rationally targeted for effective cancer prevention. Phenomenal and cutting-edge research works in different types of animal models will further refine our knowledge for selection of most promising circRNAs as pharmacologically valuable targets.